Competition in the Turkish mobile telecommunications market: Price elasticities and network substitution - Justus Haucap; Ulrich Heimeshoff; Mehmet Karaçuka (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper estimates demand elasticities for the Turkish mobile telecommunication market. In contrast to most other studies, firm level data is used to estimate dynamic panel data models including instrumental variable techniques. Both short- and long-run elasticities are calculated, yielding a long-run price elasticity of -0.72 for the post-paid market and of -0.33 for the pre-paid market. The short-run price elasticity is estimated to be -0.36 for the post-paid market and -0.20 for the pre-paid market. In addition, evidence of fixed to mobile traffic substitution is provided for consumers that use pre-paid cards.
Keywords: C23; L13; L96; 330; mobile telecommunications; price elasticity; network substitution; dynamic panel data analysis; Mobilkommunikation; Wettbewerb; Preiselastizität; Substitutionseffekt; Schätzung; Türkei